Regulation In Procurement Of Goods And Services For Amounts Up To 8 Uit Tax Units And Efficiency In Purchases Of The Social Health Security - Essalud, 2022 - Jurado, Marco Antonio Roca; Castañeda, Helen Margiori Mengoa (Journal of Neonatal Surgery, 2025)
The objective of this research is to determine the relationship that exists between the regulation in the contracting of goods and services for amounts equal to or less than eight (8) UIT and the efficiency in purchases in ESSALUD, 2022. Methodology: application type with a non- experimental and cross-sectional design for which two instruments were applied. Results: 3.3% of respondents (3) report not presenting an adequate procedure in the regulation in the contracting of goods and services for amounts equal to or less than 8 UIT, while 46.7% (42) report Sometimes an appropriate procedure is presented, 44.4% of those surveyed (40) say that it is almost always and 5.6% of those surveyed (5) say that it is always. Conclusion: it can be assured that ESSALUD has its respective regulations that correspond to Contracts Equal and Inferior to the 8 UIT, which are updated following the conditioning for an optimal process and efficiency in the purchasing processes